Cutaneous candidosis in immunosuppressed patients - Jautová, J; Baloghová, J; Dorko, E; Pilipcinec, E; Svický, E; Danko, J; Tkáciková, L (Folia microbiologica, 2001)
One-hundred patients with candidosis of the skin, mucous membranes and nail plates (confirmed by cultivation) were examined. Topical or systemic antimycotic treatment was successful in 58 patients. After a complete evaluation, 42 patients were found to suffer from factors supporting candidosis--diabetes mellitus (12), anemia (3) and various local factors (10 patients); 27 patients showed a deficiency in cell-mediated immunity. In addition to intensive antimycotic therapy, successful treatment is affected by the actual immunity level and can be ensured by efficient immunomodulation treatment of immunodeficiency.
Keywords: protilátky fungální; imunokomplex; Antibodies, Fungal; Humans; T-Lymphocytes; antifungální látky; rizikové faktory; lidé; Candidiasis, Cutaneous; fagocytóza; Antigen-Antibody Complex; Antifungal Agents; imunokompromitovaný pacient; T-lymfocyty; Immunocompromised Host; kandidóza kožní; Phagocytosis; Risk Factors; Candida